TRIPS Agreement and Pharmaceutical Patent Protection - Citrawinda, Cita (Indonesian Journal of International Law, 2008)
Promotion and improvement protections in intellectual property rights (IPRs), particularly in the developing countries with weak tradition in the protection of IPRs has become new major factor that potentially affecting state’s ability to guarantee the access to drugs. Access to drugs is the main issue in public health, especially regarding to patent that has impact on drugs prices. This article discusses how Indonesia, as one of developing countries, can ensure access and protection of the IPRs in drugs issues.